1998
DOI: 10.1071/a98015
|View full text |Cite
|
Sign up to set email alerts
|

Drying of surface soil decreased Lupinus angustifolius root length and manganese uptake in a split-root experiment

Abstract: In a glasshouse, a split-root experiment was used to determine the ability oflupins (Lupinus angustifolius L.) to take up manganese(Mn) from dry soil either when young or at mid-flowering of the primarybranches. Three soil-watering regimes (maintained at field capacity,maintained below wilting point, and alternating from field capacity to wellbelow wilting point) were imposed after taproots had grown through topsoil andinto a nutrient solution below. Four sequential harvests (11, 22, 37, and 49days after sowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Earlier work is equivocal with respect to enhanced nutrient uptake arising from hydraulic lift. Some authors reject a significant increase in nutrient uptake (Crabtree et al 1998;Grundon 1980;Simpson and Lipsett 1973;Vetterlein and Marschner 1993) whilst others observed a net increase in the uptake of immobile nutrients such as Zn and P (Matzner and Richards 1996;Nambiar 1976;Rose et al 2008;Valizadeh et al 2003). However, Nambiar (1976) found that Zn uptake from the dry surface soil by oats could be attributed to mucilage exudation.…”
Section: Hydraulic Liftmentioning
confidence: 86%
See 1 more Smart Citation
“…Earlier work is equivocal with respect to enhanced nutrient uptake arising from hydraulic lift. Some authors reject a significant increase in nutrient uptake (Crabtree et al 1998;Grundon 1980;Simpson and Lipsett 1973;Vetterlein and Marschner 1993) whilst others observed a net increase in the uptake of immobile nutrients such as Zn and P (Matzner and Richards 1996;Nambiar 1976;Rose et al 2008;Valizadeh et al 2003). However, Nambiar (1976) found that Zn uptake from the dry surface soil by oats could be attributed to mucilage exudation.…”
Section: Hydraulic Liftmentioning
confidence: 86%
“…On the contrary, enhanced root proliferation and continuing root viability accounted for significant P uptake from the surface-dried sandy soil by the cotton plant. It has been suggested that root growth is more responsible for the P uptake than P diffusion rate under waterstressed conditions (Barber and Mackay 1985;Crabtree et al 1998;Vetterlein and Marschner 1993). P uptake from the moist subsoil Compared to the sandy soil, the clay soil was relatively more fertile and held more available water.…”
Section: Hydraulic Liftmentioning
confidence: 99%
“…Some desert species have the capacity to take up nutrients from very dry soils (e.g., *-5 MPa; Matzner and Richards 1996), and Buffalo grass may be able to extract nutrients even under dry soil conditions (Huang 1999). Previous studies found that HL did not increase plant acquisition of NO 3 - (Snyder et al 2008) or other nutrients (see Online resource 1 for details; Crabtree et al 1998;Hawkins et al 2009;Rose et al 2008;Wang et al 2009), while other studies suggested that HL increased plant uptake of mineral N compounds (Dawson 1997;de Kroon et al 1998;Huang 1999;Leffler et al 2004). However, all these latter studies added labeled N as liquid pulses, and thus the nutrient could have Table 3 Plant growth parameters including root-to-shoot ratio (shoot is considered the biomass of live leaves only), specific leaf area (SLA), total N concentration in leaves and roots (mean ± 1SE; n = 6), d 15 N in leaves, stolons and roots from lower compartment (mean ± 1SE; n = 3 for stolons, n = 6 for leaves and roots) and overall above-(leaves and stolons) and below-ground plant 15 N content (mean ± 1SE; n = 5-6) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, empirical evidence of these general processes is scarce, and in the specific case of nutrient uptake, the positive role of HL is not universally supported (Online resource 1). Several studies have considered the effect of HL on nutrients indirectly (Caldwell and Manwaring 1994;Crabtree et al 1998;Dawson 1997;de Kroon et al 1998;Hawkins et al 2009;Huang 1999;Matzner and Richards 1996;Nambiar 1976;Rose et al 2008;Snyder et al 2008;Wang et al 2009), but results have been largely inconclusive for a number of reasons, including lack of suitable control treatments, restricted experimental time scales, or addition of nutrients in aqueous solution rather than in solid form (see Online resource 1 for more details).…”
Section: Introductionmentioning
confidence: 99%
“…Such a practice should increase P availability to the crop. A number of workers have reported benefits from this strategy (Crabtree et al, 1998;Crabtree, 1999;Nable and Webb, 1993;Sander and Eghbell, 1999;Teutsch et al, 2000), resulting in increased productivity and sustainability of the cropping system. However there has been no published research on the rates and depth of placement of P fertilisers for major crop species in the semiarid cropping areas of northern Australia.…”
Section: Introductionmentioning
confidence: 97%